Interrelating Ecology and Health: Some Bio-Social Concerns - Kaur, Reetinder (Ecoprint: An International Journal of Ecology, 2015)
Ecology and health issues are often characterized by complex interactions between ecosystems and social systems, and demand integration of themes that span the environmental and socioeconomic determinants of health. The present paper emphasizes the health implications of interactions between human groups and their social, physical and biological environments which help in understanding how changes and fluctuations in ecology affects rate and pattern of diseases. ECOPRINT 21: 31-40, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11902